Retention of short chain fatty acids under drying and storage conditions - Souza, Alexandre Santos (2010)
Cheese whey permeate was used as a substrate for the fermentation of Propionibacterium freudenreichi PS1 for the production of short chain fatty acids, components of the bio-aroma of Swiss cheese. The liquid bio-aroma was encapsulated by spray drying under different conditions of air inlet temperature and feed rate. A study was carried out on the stability of the bio-aroma during storage in laminated packages at 30 °C for 96 days using the product showing the greatest retention of acetic and propionic acids. The results showed that the best drying conditions were an air entrance temperature of 180 °C and a feed rate of 24 g/min resulting in particles with a smooth surface and few invaginations and micro-fissures. However, 72% of the acetic acid and 80% of the propionic acid were lost during storage showing that the wall material used was inadequate to guarantee product stability.